Representation of Nationalism in The Kubro Art Performed by The Seven Angel Kubro Art Group - Wahyuni, Dwi; Harini; Selly Rizki Yanita (Southeast Asian Language and Literature Studies, 2025)
The development of popular culture lately has an impact on local culture which is starting to be  abandoned, especially by the younger generation. Like kesenian Kubro in Ngasinan Village,  Purworejo, which was abandoned because there was no longer public enthusiasm for that art.  Kubro in Ngasinan Village has been preserved again by Grup Kesenian Kubro Tujuh Bidadari by  combining Kubro with dangdut rhythms to suit the tastes of the community. This effort is a big  thing in preserving local culture. Especially with the involvement of children who are the nation's  next generation in this effort. Thus, Kubro can be a representation of nationalism through regional  arts that are adapted to the times without losing the identity of the art. In this study, visual and  non-visual signs that represent nationalism will be analyzed. The method used in this study is a  qualitative descriptive method with a semiological approach. Based on the results of the analysis,  there are representations of nationalism found in dance moves, the costumes of dancers, and  Kubro’s song lyrics in Purworejo Regency. Based on the results of the analysis, it is hoped that the  main purpose of this art as an effort to preserve a local culture that represents nationalism as well  as entertainment for the community can be fulfilled.